Relationship Between Growth and Unemployment in Petroleum Exporting Countries: Case of Congo - Idrys Fransmel Okombi (Jurnal Ekonomi dan Studi Pembangunan, 2019)
The purpose of this article is to examine relation between growth and unemployment in Congo. To this, the error correction model ARDL is used. The estimation results show the existence of relation significantly negative between growth and long term unemployment on the period 1991.Q1-2016.Q1. Such a result accounts an unemployment existence of a structural character in Congo. In this regard, the resolution of unemployment problem in Congo goes through the policies of the offer. In other words, the Congolese government must put in place policies aiming to increase productivity of production factors. To be specific, the government can favor the augmentation of a prospective GDP, urging companies with important manpower to invest, by an increase of productive public investment. Keywords: growth, employment, ARDL, CongoJEL Classification: E23, E24, C32, 055